МЕКТЕПКЕ ШЕКЕМГИ ЖАСТАҒЫ БАЛАЛАР УШЫН ТӘРБИЯЛЫҚ ИЛАЖЛАРДЫҢ ӘҲМИЙЕТИ - Алеуова, Р.Ш.; Нишонова, Н.Ў. (FAN va JAMIYAT, 2016)
The article is devoted to the right organization of upbringing activities in preschool establishments. It contains the analysis of basic direction of upbringing activities: patriotism and legal education, moral and aesthetic upbringing; ecological upbringing; formation of healthy life style and physical training, direction to professions. The great attention is paid to the peculiarities of every direction in the organization of the activities.